2018
DOI: 10.1093/beheco/ary008
|View full text |Cite
|
Sign up to set email alerts
|

Social and ecological drivers of reproductive seasonality in geladas

Abstract: Many nonseasonally breeding mammals demonstrate some degree of synchrony in births, which is generally associated with ecological factors that mediate fecundity. However, disruptive social events, such as alpha male replacements, also have the potential to affect the timing of female reproduction. Here, we examined reproductive seasonality in a wild population of geladas () living at high altitudes in an afro-alpine ecosystem in Ethiopia. Using 9 years of demographic data (2006-2014), we determined that, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 92 publications
1
59
0
Order By: Relevance
“…Although takeovers of small units were less frequent, when they did occur, immigrant males killed disproportionately more infants than when they took over mid-sized units. In this population, male takeovers dramatically alter female reproductive patterns ( 9 , 22 ); here we show that females in mid-sized units have a selective advantage over females in smaller or larger units when it comes to these male-mediated birth patterns.…”
Section: Main Textmentioning
confidence: 54%
See 4 more Smart Citations
“…Although takeovers of small units were less frequent, when they did occur, immigrant males killed disproportionately more infants than when they took over mid-sized units. In this population, male takeovers dramatically alter female reproductive patterns ( 9 , 22 ); here we show that females in mid-sized units have a selective advantage over females in smaller or larger units when it comes to these male-mediated birth patterns.…”
Section: Main Textmentioning
confidence: 54%
“…67 +/− 0.44 SE, p -value = 0.13). Previous analysis in this population have indicated that temperature, and not the availability of green grass, most strongly predicts glucocorticoid levels ( 9 , 26 ). Therefore, thermoregulatory demands, which presumably affect all individuals equally across units of different size, may constrain metabolic needs more than food does.…”
Section: Main Textmentioning
confidence: 67%
See 3 more Smart Citations